1991
DOI: 10.1084/jem.174.5.1111
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced binding of peptide antigen to purified class II major histocompatibility glycoproteins at acidic pH.

Abstract: SllmmsryHelper T lymphocytes recognize peptide antigens stably associated with class II major histocompatibility complex (MHC) glycoproteins on the surface of antigen-presenting cells and serve to regulate a wide variety of immune responses. A previous study from our laboratory had demonstrated that the functional association of various peptide antigens with the antigen-presenting cell membrane was increased at pH 5 as compared to pH 7, consistent with the potential role of acidic endosomal compartments in ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 33 publications
5
60
0
Order By: Relevance
“…It has been suggested that the absence of "negative" amino acids may be more important than the presence of amino acids giving a "positive" interaction with MHC [58]. Also, the reported enhanced binding of peptide HEL(104 -120) at acidic pH [59], where the net charge is less negative, is in agreement with the disrupting effect on binding of Asp and Glu at several positions of the peptide at higher pH [60] where the net charge is more negative.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the absence of "negative" amino acids may be more important than the presence of amino acids giving a "positive" interaction with MHC [58]. Also, the reported enhanced binding of peptide HEL(104 -120) at acidic pH [59], where the net charge is less negative, is in agreement with the disrupting effect on binding of Asp and Glu at several positions of the peptide at higher pH [60] where the net charge is more negative.…”
Section: Discussionmentioning
confidence: 99%
“…Unilamellar liposomes containing purified DR1 and/or DM were generated as described in Materials and Methods. Samples containing identical quantities of DM and DR1 distributed together or separately into liposomes were incubated for 3 h at pH 5 with 1 M biotin-MAT (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) peptide. After chilling on ice, liposomes were solubilized in 1% NP40 and biotin-MAT-DR1 complexes were quantified by europium fluorescence immunoassay (f).…”
Section: Discussionmentioning
confidence: 99%
“…DR1-biotin CLIP complexes were formed by incubation of 500 nM DR1 with 5 M biotin-CLIP for 18 h at 37°C. For dissociation, preformed complexes were diluted 10-fold and incubated in 20-l volumes with 100 M unlabeled MAT (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). After neutralization, the complexes were captured on L243-coated microtiter wells at 4°C and biotin complexes were measured with streptavidin-europium as previously described (5).…”
Section: Peptide Dissociation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigen processing by APC can be inhibited with reagents including chloroquine, monensine and NH4CI that elevate intracellular pH [8]. These acidic conditions are required for efficient antigen presentation, partly to provide the optimum conditions for acidic enzymes which process both invariant chain (Ii) [9,10] and antigen [7,10], and partly to facilitate peptides binding to MHC class II [11 ]. Early studies employing mutant hamster ovary cells suggested that acidification of early endosomes was an important event in antigen processing [12].…”
Section: Introductionmentioning
confidence: 99%